1999
DOI: 10.1002/(sici)1521-3765(19990201)5:2<599::aid-chem599>3.0.co;2-n
|View full text |Cite
|
Sign up to set email alerts
|

Total Synthesis of Brevetoxin A: Part 1: First Generation Strategy and Construction of BCD Ring System

Abstract: Discussed herein is our first generation strategy for the total synthesis of brevetoxin A. This approach relies upon dissection of the molecule at the nine-membered ring site (ring E). A Wittig coupling of requisite polycyclic fragments 3 and 4 followed by hydroxy dithioketal cyclization was expected to furnish the polycyclic framework of brevetoxin A (1). Intermediate 8 was anticipated to be a valid synthetic precursor to phosphonium salt 3, and its synthesis was accomplished by a bis(lactonization)/ thionola… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0
1

Year Published

1999
1999
2020
2020

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 93 publications
(25 citation statements)
references
References 22 publications
1
23
0
1
Order By: Relevance
“…Following the procedure described by Nicolaou et al [ 18 ] we attempted the opening of the epoxide to obtain a dihydroxylated compound in C-4 and C-5. Unexpectedly, the integrals of the 1 H-NMR of the product showed that there was only one hydrogen at C-6 at δ 4.77 (H-6), too high for hydrogens in α position to the carbonyl at C-1.…”
Section: Resultsmentioning
confidence: 99%
“…Following the procedure described by Nicolaou et al [ 18 ] we attempted the opening of the epoxide to obtain a dihydroxylated compound in C-4 and C-5. Unexpectedly, the integrals of the 1 H-NMR of the product showed that there was only one hydrogen at C-6 at δ 4.77 (H-6), too high for hydrogens in α position to the carbonyl at C-1.…”
Section: Resultsmentioning
confidence: 99%
“…The vinyliodide fragment 27 lacking the C‐11 methyl branch (amphidinolide X numbering) was obtained by alkylation of 2‐methyl‐1,3‐dithiane 20 with ( S )‐ 21 (>99 % ee )33 followed by opening of the epoxide in 22 with propynyl lithium in the presence of BF 3 (OEt 2 ) (Scheme ) 34. 35 Treatment of 23 with ethyleneglycol and iodine in MeCN gently swapped the thioketal for the corresponding 1,3‐dioxolane 24 ,36, 37 which served as the substrate for a subsequent hydrozirconation/iodination38 sequence once the free hydroxy group had been protected as PMB‐ether. For a regioselective hydrozirconation of a non‐symmetrical alkyne to occur, it is believed that thermodynamic conditions need to be operative 38.…”
Section: Resultsmentioning
confidence: 99%
“…[ α ]${{{20\hfill \atop {\rm D}\hfill}}}$ =−6.4 ( c =4.2, CH 2 Cl 2 ) [lit. :36 [ α ]${{{22\hfill \atop {\rm D}\hfill}}}$ =−4.9 ( c =4.7, CH 2 Cl 2 )]; 1 H NMR (400 MHz, CDCl 3 ): δ =3.20–3.16 (m, 1 H), 2.95–2.79 (m, 5 H), 2.52 (dd, J =5.0, 2.7 Hz, 1 H), 2.23 (dd, J =14.7, 4.8 Hz, 1 H), 2.10 (dd, J =14.7, 6.3 Hz, 1 H), 2.06–1.87 (m, 2 H), 1.71 ppm (s, 3 H); 13 C NMR (100 MHz, CDCl 3 ): δ =48.7, 47.4, 46.3, 44.0, 28.1, 26.3, 26.2, 24.6 ppm; IR (film): $\tilde \nu $ =3045, 2920, 1446, 1422, 1277, 1258, 864 cm −1 ; MS (EI): m / z (%): 190 (41) [ M + ], 133 (100); HRMS (EI): m / z: calcd for C 8 H 14 OS 2 [ M + ]: 190.0486, found: 190.0488.…”
Section: Methodsmentioning
confidence: 99%
“…By using this gap in methodology as an opportunity for discovery, we developed a series of synthetic reactions based on the power of heteroatoms (i.e., sulfur and phosphorous) to drive these entropically disfavored ring closures; four of these methods are shown in Scheme 2. Apart from finding widespread applicability to a range of other synthetic problems, these unique approaches were critical to the completion of both of these formidable targets, accomplishments that have more recently inspired a host of researchers to attempt the total synthesis of other cyclic polyethers, some of even greater size and complexity (14)(15)(16)(17)(18)(19)(20).…”
Section: Selected Total Synthesis Endeavorsmentioning
confidence: 99%